Nimotuzumab Increases the Recovery Rate of Severe and Critical COVID-19 Patients: Evaluation in the Real-World Scenario - Diaz, Henrry; Jiménez, Jorge; Hernández, Aray; Valdés, Leivis; Martínez, Ariadna; Porto, Leonor; Hernández, Raity; Travieso, Nadina; Jova, Julio Héctor; Medel, Loipa; Troche, Mayelin; Gorte, Annia; et al. (Frontiers in Public Health, 2022)
EGFR signaling is an important regulator of SARS-CoV induced lung damage, inflammation and fibrosis. Nimotuzumab is a humanized anti-EGFR antibody registered for several cancer indications. An expanded access study was conducted to evaluate the safety and recovery rate of severe and critical patients with confirmed SARS-CoV-2 infection, treated with nimotuzumab in combination with the standard of care in the real-world scenario. The antibody was administered as an intravenous infusions every 72 hours, up to 5 doses. In order to assess the impact of nimotuzumab, the recovery rate was compared with a paired retrospective cohort. Control patients received standard treatment according the national protocol but not nimotuzumab. Overall, 1151 severe or critical patients received nimotuzumab in 21 hospitals of Cuba. Median age was 65 and 773 patients had at least one comorbidity. Nimotuzumab was very well tolerated and mild or moderate adverse events were detected in 19 patients. 1009 controls matching with the nimotuzumab patients, were selected using a “propensity score” method. The 14-day recovery rate of the nimotuzumab cohort was 72 % vs. 42 % in the control group. Controls had a higher mortality risk (RR 2.08, 95% CI: 1.79, 2.38) than the nimotuzumab treated patients. The attributable fraction was 0.52 (95% CI: 0.44%; 0.58), and indicates the proportion of deaths that were prevented with nimotuzumab. Our preliminary results suggest that nimotuzumab is a safe antibody that can reduce the mortality of severe and critical COVID-19 patients.